Circular aluminium & mild steel tubes with die radius of 10 mm for energy absorption. (2021) - Manjunatha, G.; Sharath, G.S.; Reddy, K. Sharan Teja
Abstract: In different engineering applications usage of Circular Aluminium & Mild Steel tubes as impact energy absorbers is encouraged. These are easily available in numerous cross sections and sizes. Energy absorption capacity under quasi-static and dynamic loads is also high. Current experiment is on behavior of circular aluminum and mild steel tubes when subjected to axial load under quasi-static. Axial load is applied on tubes placed between a circular flat plate and a die of radius 10 mm. Then different stages of deformation is observed and energy absorption of same is calculated.